PROFILE ADAPTIVE MODULE OF UNIVERSITY ORGANIZATIONAL CULTURE - Dmitry N. Bezgodov (Moscow Polytechnic University, 2016)
The article presents a special educational, social and communicative project aimed at students' adaptation to corporate culture of the largest employing organizations. Adaptation of a university graduate to a workplace means assimilation of corporate values and organizational culture of an employer. We have elaborated a unique model that enables students of Ukhta State Technical University to adapt successfully to working environment. The profile module of university organizational culture can easily be adapted to specific profile of employing organization. We also have worked out a supplementary training program for student activists "Organizational culture management" for mastering their management skills. The program includes a theoretical course (foundations of organizational culture, motivation theory, axiology, theory of symbols, communication theory, psychology of small groups, team building methods, project management tools, symbolic capital theory) and a module for practical training.